Літературна персоналістика «Я-автора» та героя у повісті «Пожар» В. Распутіна - Кузава, Ігор; Kuzava, Igor (Східноєвропейський національний університет імені Лесі Українки, 2015)
Стаття присвячена характеристиці Я-автора та героя у повісті «Пожар» В. Распутіна. Визначено їх роль, місце і вплив на жанрову структуру та ідейно - естетичну своєрідність твору. Розглянуто роль кризової свідомості на зміст художнього мислення. Запропоновано перспективи подальшого дослідження проблеми. The article is devoted to the characterization of "I-authora" and the hero of the V. Rasputin's story "Fires". Denned their role, place and influence on the genre structure and ideological and aesthetic originality of the work. Showing degree of relationship "I-authora" and the character of the work. It was found that through direct preaching in the text at the forefront of the political and ethical functions, and outright civil publicistic pathos enters and removes reflections "I-authora" the socio-historical level. The role of awareness of crisis on the content of creative thinking. An important place is given to thinking "I-authora" the meaning of life, the role and place of man in the environment as the person being tested disasters, war, famine early postwar years and fire. The role and place in the structure of time-space work, which constantly interwoven time frames. A further study on prospects.
Literary Personalistyka of the "I-authora" and the Hero in the V. Rasputin's Story "Fires"
Keywords: Я-автора; герой; I-authora; character